L’adaptation au changement climatique en zone côtière selon l’approche communautaire : études de cas de projets de recherche-action participative au Nouveau-Brunswick (Canada) - Omer Chouinard; Sebastian Weissenberger; Dan Lane (VertigO)
This article will present case studies of collaborative action research projects on adaptation to climate change, erosion and sea level rise in coastal and riverine communities in New Brunswick. Those communities are Bathurst/Bayshore, Shippagan, Le Goulet, Cocagne, Grand-Digue, Shediac and Perth-Andover. The projects were lead by researchers from the University of Moncton, in collaboration with other establishments, adopting a participatory research-action approach. The analysis of the case study will aim at understanding the importance of the participation of communities in the elaboration of adaptation strategies and identify certain recurrent themes in the empirical corpus.